University Evolution, Entrepreneurial Activity and Regional Competitiveness - Audretsch, David; Lehmann, Erik; Meoli, Michele; Vismara, Silvio (International Studies in Entrepreneurship, 2016)
XIII, 447 p. 42 illus.